Engineering the electronic structure of graphene - Zhan, Da (2013)
Graphene exhibits many unique electronic properties owing to its linear dispersive electronic band structure around the Dirac point, making it one of the most studied materials in the last 5-6 years. However, for many applications of graphene, further tuning its electronic band structure is necessary and has been extensively studied ever since graphene was first isolated experimentally. Here we review the major progresses made in electronic structure engineering of graphene, namely by electric and magnetic fields, chemical intercalation and adsorption, stacking geometry, edge-chirality, defects, as well as strain.